Pelatihan Penyusunan Laporan Kelayakan Usaha Tata Busana Bagi Warga Belajar Non-Formal di Kecamatan Peureulak Timur Kabupaten Aceh Timur - Jamali; Ismail; Sakinah, Dinda; Suhaina (PASAI : Jurnal Pengabdian kepada Masyarakat, 2022)
Empowerment of Learning Citizens in preparing small scale home industry businesses in the fashion sector is very important and strategic in developing a people's economy for people who drop out of school or through non-formal education. The Home Industry business is still very difficult to develop because the competence of business owners is still lacking in managing the business, this needs government attention for people who want to develop a business in the fashion sector, and there is no business companion by the same business that is already running well or can be through strengthening Community Learning Activity Center in this case PKBM Purnama Raya, so that their business development can run well. For the success of the goals and objectives of this PKM activity, several approach methods are carried out such as problem identification, Preliminary Survey, Evaluation and Report of results. Based on the results of the training activities obtained: 1) there is an increase in knowledge and understanding of the importance of preparing good and correct reporting; 2) the ability to prepare reports on business feasibility studies increases; 3) the value of the results of independent reporting processing can be used for financing by Donors. The Business Feasibility Study Report is very much needed by Donors to avoid the risk of loss by seeing whether or not a business is carried out in a sustainable manner. This Business Feasibility Study Report also makes it easier for Donors to plan, monitor and follow up their business